The utility of an interprofessional education framework and its impacts upon perceived readiness of graduates for collaborative practice. A multimethod evaluation using the context, input, process, product (CIPP) model. (February 2023) - Meiklejohn, Sarah; Anderson, Amanda; Brock, Tina; Kumar, Arunaz; Maddock, Bronwyn; Wright, Caroline; Walker, Lorraine; Kent, Fiona
Abstract: Background: Frameworks in higher education can support strategic curriculum change in complex systems. The impact of these frameworks in achieving their stated purpose is less known. An interprofessional education (IPE) framework and related multi-activity curriculum designed to develop health profession graduates with the requisite skills for collaborative care, was introduced in a large university, across eleven health professions. Objective: To determine the utility of an interprofessional framework and impact upon perceived work readiness for collaborative practice. Method: A multimethod design using the context, input, process, product (CIPP) evaluation model was selected taking a social constructivist theoretical stance. Data collection included staffing allocation to IPE, curriculum audit, and reflections from representatives of all health professions courses offered at the institution. Data was analyzed using framework analysis. Participants: Interviews or focus groups were undertaken with academic Faculty (n = 13), recent graduates (n = 24) and clinical supervisors/employers of recent graduates (n = 17). Results: The framework assisted the systematic implementation of interprofessional curriculum across the different health courses at the university. Collaborative work-ready learning outcomes were identified in graduates where targeted curriculum had been implemented across all four domains of the framework. Gaps identified in framework implementation were consistent with gaps identified in graduate knowledge and skills related to collaborative practice. The combination of formal university-based IPE and informal workplace learning as part of clinical placements contributed to achieving the desired learning outcomes. Conclusions: These findings offer insights into the use of shared frameworks to drive specific learning activities related to collaborative practice.